Large-Scale Conformational Changes and Protein Function: Breaking the in silico Barrier - Orellana, Laura (Frontiers in Molecular Biosciences, 2019)
Large-scale conformational changes are essential to link protein structures with their function at the cell and organism scale, but have been elusive both experimentally and computationally. Over the past few years cryo-electron microscopy and novel crystallography techniques have started to reveal multiple snapshots of increasingly large and flexible systems, deemed impossible only short time ago. As structural information accumulates, theoretical methods become central to understand how different conformers interconvert to mediate biological function. Here we briefly survey current in silico methods to tackle large conformational changes, reviewing recent examples of cross-validation of experiments and computational predictions, which show how the integration of different scale simulations with biological information is already starting to break the barriers between the in silico, in vitro and in vivo worlds, shedding new light onto complex biological problems inaccessible so far.